Degree of Brine Evaporation and Origin of the Mengyejing Potash Deposit: Evidence from Fluid Inclusions in Halite. (February 2017) - SHEN, Lijian; LIU, Chenglin; WANG, Licheng; HU, Yufei; HU, Mingyue; FENG, Yuexing
Abstract : Abstract: The Mengyejing potash deposit is located in the southern port of the Simao Basin, Yunnan Province, and is hosted in mid‐Cretaceous strata. The chemical compositions of fluid inclusions in halite crystals, collected from the level‐610 adit in the deposit, were analysed by laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS). The results show that the brine is of the Na‐K‐Mg‐Ca‐Cl type and has K concentrations that are distinctly higher than those of Mg and Ca, unlike normal brines associated with Cretaceous halite. The high K concentrations indicate that the degree of evaporation of the ancient Mengyejing saline lake was very high, reaching the sylvite deposition stage but rarely reaching the carnallite deposition stage. The trajectory of the H and O isotopic compositions of the brines in the halite‐hosted fluid inclusions corresponds to intense evaporation, indicating that the net evaporation exceeded the net inflow of brines. These brine compositions in halite‐hosted fluid inclusions were likely formed by the dissolution of previously deposited K‐bearing minerals by fresh continental and/or seawater, forming a type of modified seawater, with deep hydrothermal fluids potentially supplying additional potassium. The basin likely experienced multiple seawater incursion, dissolution and redeposition events in a high‐temperature environment with high evaporation rates.